Changes in peroxisome proliferator-activated receptor alpha target gene expression in peripheral blood mononuclear cells associated with non-alcoholic fatty liver disease - Tian Tian Li; Tian Bi Tan; Hai Qing Hou; Xiao Yun Zhao (Lipids in Health and Disease, 2018)
Abstract Objective To identify differences in the expression of peroxisome proliferator-activated receptor alpha (PPARα) target genes in human peripheral blood mononuclear cells (PBMCs) associated with non-alcoholic fatty liver disease (NAFLD) among Chinese individuals. Methods Thirty healthy subjects were selected as the control group (CN), and 43 patients newly diagnosed with NAFLD were subdivided into two groups, non-obese group (NF, n = 21) and obese group (OF, n = 22). Expression of PPARα and its target genes was determined in PBMCs. The levels of liver cell damage markers, total cholesterol (TC), triglyceride (TG), free fatty acids (FFA), glucose, and insulin were determined in serum. Results Compared to the CN group, the blood pressure and homeostasis model assessment for insulin resistance (HOMA-IR) were increased in the other groups (P < 0.05), while the systolic blood pressure (SBP) and liver cell damage markers were significantly increased in the OF group (P < 0.05). In the OF group, PPARα target gene expression was 2.03–3.31 times higher than that in the CN group, and a negative correlation was found between PPARα target gene expression and abdominal circumference (AC), body mass index (BMI), diastolic blood pressure (DBP). Additionally, solute carrier family 25 (carnitine/acylcarnitine translocase) member 20 (SLC25A20) and acyl-coenzyme A dehydrogenase 2 long chain (ACADVL) were negatively correlated with HOMA-IR; PPARα, acetyl-coenzyme A dehydrogenase 2 (ACAA2), and carnitine palmitoyltransferase 1A (CPT1A) were positively correlated with HOMA-IR. Conclusion There is an up-expression of PPARα target genes in the PBMCs of NAFLD patients, possibly leading to changes in β-oxidation and insulin resistance.